Riesgo cardiovascular en mujeres menopáusicas utilizando las tablas de Framingham por categorías de Wilson y su estrecha relación con los factores socioeconómicos - Ortiz Argandoña, Amparo Micaela (2015)
The principal objective of this investigation has been the analysis of cardiovascular risk in menopause women and relationship with the socioeconomic facts actually, through Framinghan´s tables by Wilson´s categories, realized in the Isidro Ayora Hospital from Loja between January and June 2015. Beginning to investigate to eighty women that are feeling menopause and recollection of important facts how taking blood pressure and complementaries examinations (Total cholesterol and HDL) it is determined the percentage of cardiovascular risk and these in turn are correlationed them with other socioeconomic facts, the cardiovascular risk to increase drastic in women are fifty years old and to become moderated in 27,50 percentage and severe in 16,25 percentage and it is in women that are unfavorable level of socioeconomic and education is low too. It is not overcome the high – school 42,50 percentage of women practice domestic chores with their low status 21,25 percentage and less economic income to 550.00 dollars monthly of the 41,25 percentage.